Citizenship and the Reproductive Body: Law, Identity, and Nation in Contemporary India - AGGYA PANDEYA (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2026)
The relationship between citizenship, reproductive rights, and national identity has become a significant topic in Indian politics today. The reproductive body is not just a matter of the individual, but a space where law, politics, gender, religion, and nationalism intersect. Questions of fertility, maternity, population control, abortion, surrogacy, and birth control have emerged as political matters that concern citizenship and belonging. In India, the laws and policies about reproduction are socially stratified along lines of caste, religion, social class, and gender, thereby producing inequalities in citizenship. The reproductive body of the woman, especially those of marginalised groups, becomes the site of regulation and politics of citizenship. This essay seeks to understand the influence of reproductive governance on national identity and citizenship in contemporary India. It explores reproductive governance from a legal and political perspective and examines how the ideal citizen, family, and nation are formed in laws concerning reproduction.